Fractionation of tick saliva reveals proteins associated with the development of acquired resistance to Ixodes scapularis. Issue 51 (3rd December 2020) - Černý, Jiří; Lynn, Geoffrey; DePonte, Kathleen; Ledizet, Michel; Narasimhan, Sukanya; Fikrig, Erol
Highlights: Some but not all tick saliva fractions are able to induce tick protective immunity. Its level is comparable to those induced by whole saliva. 24 salivary proteins were detected only immunogenic fractions. These proteins pose promising candidates for tick vaccine development. Abstract: Tick-borne diseases pose a global medical problem. As transmission of tick-borne pathogens to their hosts occurs during tick feeding, development of vaccines thwarting this process could potentially prevent transmission of multiple tick-borne pathogens. The idea of tick vaccines is based on the phenomenon of acquired tick immunity, rejection of ticks feeding on hosts which were repeatedly infested by ticks. Recently, we demonstrated that saliva of the blacklegged tick Ixodes scapularis, which is the main vector of tick-borne pathogens in northeast USA, is sufficient for induction of tick immunity in the guinea pig model and that immunity directed against tick glycoproteins is important in this phenomenon. Nevertheless, immunity elicited against individual tick salivary antigens, which have been identified and tested so far, provided only modest tick rejection. We therefore now tested fractions of tick saliva produced by liquid chromatography for their ability to induce tick immunity in the guinea pig model. Immunization with all individual fractions elicited antibodies that reacted with tick saliva, however only some fractions displayed the ability to induce robust protective tick immunity. Mass spectrometry analysis led to identification of 24 proteins present only in saliva fractions which were able to induce tick immunity, suggesting suitable candidates for development of a tick vaccine.